Hey Arnold! Season 3 [videorecording (DVD)] - Bartlett, Craig (Paramount, 2018)
Arnold and company are back for another season of adventure, mystery, and fun down on the block. Season Three finds the gang getting a healthy dose of life lessons when Gerald gets his tonsils out, Helga reveals her true feelings for Arnold on his answering machine, Eugene and Arnold get trapped on a roller coaster, Arnold and Helga play best man and maid of honor at Coach Wittenberg's wedding, and more.